Menggagas Pendidikan Multikultur di Indonesia - Anin Nurhayati (IAIN Ponorogo, 2011)
Indonesia with diversity of ethnic, culture, tradition, social group, religion, and so on, on the one hand, has aroused the dynamics of cultural diversity and positive civilization; on the other hand, it will even become the cause of conflict and disintegration, if it is not managed wisely and comprehensively. Multicultural education in Indonesia, however, should not only become an academic discourse, but it needs to be implemented in the concrete sphere, among them is in the education realm. Here, we need a conceptual frame in its implementation, so that the problem that emerges as the effect of the diversity and religiousness bias does not become a heavy burden of this nation. Multicultural education is a reform as well as the process of education which inculcate to the students the values and beliefs the importance of uniqueness recognition at every ethnic, culture, and other social groups. There are at least five scopes in multicultural education, they are (1) promotion to strengthen cultural diversity; (2) promotion to respect human right and other different people; (3) promotion to act based on his own way of life for every human being; and (5) promotion to the importance of equality and distribution of authority among different social groups.